2017
DOI: 10.1021/acs.chemmater.7b03585
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Steam Annealing of Metal Oxide Thin Films from Aqueous Precursors: Enhanced Counterion Removal, Resistance to Water Absorption, and Dielectric Constant

Abstract: Aqueous solution deposition has emerged as a potentially scalable, high-throughput route to functional metal oxide thin films. Aqueous routes, however, generally require elevated processing temperatures to produce fully condensed films that are resistant to water absorption. Herein, we report a low-processing-temperature method for preparing more fully condensed, stable metal oxide films from aqueous precursors. We show that a steam anneal at ≤200 °C reduces residual nitrates in zinc oxide, yttrium aluminum ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 61 publications
(80 reference statements)
1
9
0
Order By: Relevance
“…Films were observed to be smooth and uniform on the length scale of the resolution of the SEM image, which is estimated to be 5 nm based on the size of the gaps resolvable between the grains of the Al coating. This is similar to what has been observed for other thin-film oxides prepared using PIC. ,,, In situ XRR measurements of LiAlO thin films (Figure S4) show that the film densities approach those reported for γ-phase LiAlO prepared at ambient pressure suggesting that the films are comparably dense and free of major voids despite the rapid densification and film shrinkage associated with film formation via PIC chemistries. Furthermore, obvious signs of cracking are absent in LiAlO thin films despite rapid dehydration and counter ion elimination.…”
Section: Resultssupporting
confidence: 83%
“…Films were observed to be smooth and uniform on the length scale of the resolution of the SEM image, which is estimated to be 5 nm based on the size of the gaps resolvable between the grains of the Al coating. This is similar to what has been observed for other thin-film oxides prepared using PIC. ,,, In situ XRR measurements of LiAlO thin films (Figure S4) show that the film densities approach those reported for γ-phase LiAlO prepared at ambient pressure suggesting that the films are comparably dense and free of major voids despite the rapid densification and film shrinkage associated with film formation via PIC chemistries. Furthermore, obvious signs of cracking are absent in LiAlO thin films despite rapid dehydration and counter ion elimination.…”
Section: Resultssupporting
confidence: 83%
“…As seen in Figure 10A, the transition from the W layer to the erbia layer is clearly defined, and the internal structure of the erbia coating was porous, filled with voids throughout. Existence of these voids likely results from the fairly aggressive heating rate used (10 °C/min), and this observation has been noted in metalnitrate thin films annealed at rates >25 °C/min, 15 leading to increased porosity due to rapid desorption of gaseous species during decomposition. 17 Eventually, the transition to the SS304 coupon became visible when the voids suddenly stopped appearing.…”
Section: Cross Sections Of Erbia and Yttria Coatings By Focused Ion B...mentioning
confidence: 91%
“…Cochran et al showed from TGA experiments that transition metal nitrates decompose at T < 300 °C, but rare-earths require T > 500 °C. Other important factors include temperature ramp profiles and atmospheric control during annealing to control both the densification and amount of subsurface porosity in the metal oxide coating . There is also the compatibility between coating and substrate to consider, given that coefficients of thermal expansion (CTE) at high temperature become increasingly important to maintain strong adhesion between the two materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For more complex systems such as those based on ternary or quaternary amorphous oxides (e.g., In 2 O 3 -Ga 2 O 3 -ZnO), high carrier mobilities are also possible using low processing temperatures. [5,35,[77][78][79][80][81] During the last years, the group of Prof. Calzada (female) has carried out an ambitious investigation in the field of the low-temperature crystallization of ferroelectric oxide thin films by CSD methods. We have attained for these films the 400C integration barrier (Fig.…”
Section: Introductionmentioning
confidence: 99%